Transcriptomic landscape of staminate catkins development during overwintering process in Betula platyphylla - Zhang, Jingyun; Shi, Jiayuan; Zeng, Kehao; Cai, Mengjie; Lan, Xingguo (Frontiers in Plant Science, 2024)
Betula platyphylla, belonging to the cold-specialized lineage Betulaceae, exhibits a unique reproductive strategy where staminate catkins emerge in the first summer and undergo an overwintering process, culminating in flowering in the following year. However, the underlying regulatory mechanism remains unclear. In this study, we investigated the male germline development of B. platyphylla in four distinct stages: microsporocytes in Oct. (S1), uninuclear microspores from Dec. (S2) to Mar. of the following year (S3), and bicellular microspores in Apr. (S4). We performed RNA sequencing on mature pollen and the four stages of staminate catkins. Using weighted gene co-expression network analysis (WGCNA), we identified five highly correlated gene modules with distinct expression profiles. These modules exhibited strong correlations with sugar metabolism, cell cycle, flowering, and cell wall dynamics, highlighting their dynamic roles during male germline developmental stages. During the overwintering process, we observed that the expression of transcription factors such as BpDUO1 and BpAMS at the appropriate developmental stages, suggests their significant roles in male germline development. The expression patterns of BpFLC and BpFT suggest their potential involvement in temperature perception during male reproductive development. These findings offer valuable insights into the reproductive success of plants adapting to cold environments.